Seawater carbonate chemistry and influence of periostracum cover, pH and simulated abrasion of periostracum on external shell dissolution at Marshall Gulch Beach, CA - Saley, Alisha M; Ninokawa, Aaron; Doan, Abigail; Gaylord, B (PANGAEA, 2025)
We tested this hypothesis in adult California mussels, Mytilus californianus. We quantified shell dissolution rates as a function of periostracum cover across three levels of reduced pH (7.7, 7.5, and 7.4 on the total scale). Since periostracum can also be eroded over time, we additionally conducted a first-pass examination of whether differing surface textures induced by abrasional processes might influence dissolution rates. We contextualized this set of experiments with measurements of mussel periostracum cover in multiple intertidal habitats. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were downloaded from Biological and Chemical Oceanography Data Management Office (see Source) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-08-19.
Keywords: Animalia; Benthic animals; Benthos; Calcification/Dissolution; Coast and continental shelf; Growth/Morphology; Laboratory experiment; Mollusca; Mytilus californianus; North Pacific; Single species; Temperate